Reconceptualizing Traditional Entrepreneurial Models for Women’s Economic Empowerment in Madura - Vera Firdaus; Aisyah Aisyah; Dwi Nastiti (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to identify the economic empowerment model of Madurese women by examining their entrepreneurial traditions, work culture, and self-efficacy. Women’s economic empowerment is a global issue highlighted in the Sustainable Development Goals (SDGs), particularly in SDG 8, which focuses on promoting decent work and economic growth. Enhancing women's economic participation contribute to overall economic development by generating employment opportunities in both large-scale industries and micro, small, and medium enterprises (MSMEs). Furthermore, women's empowerment aligns with SDG 5 on gender equality, emphasizing equal access to employment, education, self-actualization, leadership roles, and economic resources. This study underscores the urgency of facilitating women’s transformation into economically empowered individuals through entrepreneurship. A quantitative research design is employed, with primary data collected through questionnaires and supplemented by interviews, observations. The study’s population of consists of Madurese women from 10 sub-districts in Bangkalan. Using a multistage cluster sampling technique, 124 respondents were selected from five regions. Data analysis was conducted using multiple regression analysis, processed through Amos Structural Equation Modeling (SEM). The findings reveal that women's economic conditions and work culture significantly influence the entrepreneurial empowerment model. Moreover, the findings demonstrate that self-efficacy plays crucial role in directly enhancing the impact of women's economic empowerment on their entrepreneurial traditions.